THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS TO THE QUALITY OF FINANCIAL STATEMENTS IN MANUFACTURING COMPANIES IN INDONESIA - Benediktus Rolando; Ignatius Septo Pramesworo; Rina Apriliani; Mohamad Khairi Bin Haji Othman (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study discusses the effect of the application of Financial Accounting Standards (SAK) on the quality of financial statements of manufacturing companies in Indonesia. The research method used is literature review. The research findings show that companies that consistently apply SAK are able to produce more transparent, accurate, and comparable reports. Strict application of SAK also contributes to reducing record errors and manipulation of financial statements, improving information disclosure, and assisting stakeholders' economic decision making. This research confirms the importance of investment in accounting information technology and human resource training to support effective implementation of SAKs. The implication is that company management needs to commit to applicable accounting standards and invest in technology development and employee training to ensure reliable financial statements and improve the company's reputation and long-term competitiveness.